Detection of Hazards Endangering Some Coastal Areas: Ecosystem-Based Solutions to Strengthen Natural Defenses - Rakha, Ahmed El Sayed Ahmed (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 4, 2023)
The Nile delta's coastal strip has historically been vulnerable to environmental hazards. The main threat posed by the effects of global warming is the invasion of seawater. The removal of coastal dunes, which serve as natural protection, has accelerated the negative effects that have been visible on low-lying lands. To identify the risks associated with climate change that endanger some naturally protected coastal areas in the central part of the Nile Delta and to estimate their magnitude, field surveys, interpretation of Landsat enhanced thematic mapper imageries (ETM), and hydrochemistry analysis of water samples were used. Ecosystem-based adaptation strategies are more useful in the case of vulnerability, risk of flooding, storm surge, and the conservation and protection of coastal resources. Planting protected areas of the coastal strip is regarded as the most appropriate ecosystem-based and beneficial solution that should be authorized and implemented by local authorities in order to preserve those areas and adapt to these disasters.